The Impact of Exposure on Second Language Acquisition - Ahmad Jahrani; Rina Listia (Institut Agama Islam Negeri Palopo, 2023)
Exposure to English is something that learners experience in their daily lives. When they are doing their everyday activities, they will encounter English words. When they watch television, listen to a song, play games, or scroll through social media, they are exposed to English and this exposure can affect their second language acquisition. Many research articles have been published on the relationship between exposure and second language acquisition. However, there is no consensus on the effect exposure has on second language acquisition. By reviewing available research publications, this study sought to describe the impact of exposure on second language acquisition. The researcher employed a systematic literature review method to discover the link between all of the publications. The objective of this research is to determine the impact of exposure on second language acquisition. The publications reviewed demonstrated that exposure had a positive impact on second language acquisition. The majority of the publications reviewed stated that exposure helps with second language learning. Language exposure is necessary for learning and mastering a second language. Finally, the majority of the publications reviewed agree that exposure aids in the acquisition of a second language. Learners with extensive exposure to the language have a greater probability of speaking and comprehending it.